2022
DOI: 10.1002/jmv.27834
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus and adenovirus prevalence in patients with acute viral gastroenteritis in Denizli, Turkey, 2017–2021

Abstract: This study aims to determine retrospectively the prevalence of rotavirus and enteric adenovirus in patients with gastroenteritis symptoms and the distribution of pathogens by gender, age, seasons, and years. The stool samples sent to Pamukkale University Healthcare Research and Practice Hospital's Medical Microbiology laboratory between January 2017 and December 2021 were evaluated for rotavirus/adenovirus antigen positivity. Rotavirus and adenovirus antigens were studied with the Rotavirus-Adenovirus Combo Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…In relation to the gender factor, boys (41.1%) were tending to be more effected by rotavirus comparing to girls (33.3%). These boy predominate in the present study was in agreement with the results of some local studies [34][35][36][37][38] and some regional neighboring countries also was in agreement with our result that boys are predominant over girls e in infecting with the rotavirus gastroenteritis [39][40][41][42][43] A correlation between the occurrence of rotavirus diarrhea and boy gender has been shown in various research, in addition to other factors including poor education levels, filthy drinking water, and inadequate sanitation [44].…”
Section: Discussionsupporting
confidence: 93%
“…In relation to the gender factor, boys (41.1%) were tending to be more effected by rotavirus comparing to girls (33.3%). These boy predominate in the present study was in agreement with the results of some local studies [34][35][36][37][38] and some regional neighboring countries also was in agreement with our result that boys are predominant over girls e in infecting with the rotavirus gastroenteritis [39][40][41][42][43] A correlation between the occurrence of rotavirus diarrhea and boy gender has been shown in various research, in addition to other factors including poor education levels, filthy drinking water, and inadequate sanitation [44].…”
Section: Discussionsupporting
confidence: 93%
“…The seasonal pattern of the rotavirus varies according to the climate zone and is also associated with local weather. [21] In study in China revealed that adenovirus was detected throughout the year and there was no seasonal pattern or any peak in frequency of adenovirus through the year. [36] Furthermore, enteric adenoviral gastroenteritis in most parts of the world was documented throughout the entire year and does not display seasonal distribution.…”
Section: Discussionmentioning
confidence: 97%
“…[20] In Turkey, the prevalence of rotavirus is reported to vary between 6.7% and 20.2% and the prevalence of adenovirus between 0.96% and 7.6%. [21] According to studies conducted in Turkey, rotavirus infections constituted 9.8-39.8% of viral gastroenteritis infections, and adenovirus infections 7.8-10.0%. [22][23][24][25] In the study conducted by Öner et al [21] ,which included a 4-year period published in 2022, on children and adults, rotavirus antigen was found to be 8.2%, adenovirus antigen was 2.2% in stool samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies report that diarrhea is an independent risk factor, primarily due to the dehydration and electrolyte imbalance it causes. 17 Infants and toddlers are especially vulnerable because their daily fluid needs are high-requiring 100 to 160 mL per kilogram of body weight. The fluid loss caused by vomiting and diarrhea can quickly reach up to 3 times the circulating blood volume, rapidly leading to dehydration and disturbance in electrolyte homeostasis, circulatory function, and organ and tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%